CLIL-Based Learning Tools Mediated by Asynchronous Video for Multicultural Education in Bilingual Elementary Teacher Preparation - Novi Setyasto; Zhao Xinzhe (Sakura Digital Nusantara, 2026)
Purpose: This study developed, validated, and evaluated CLIL-based learning tools (a semester learning plan, eight thematic teaching modules, and assessment instruments) mediated by asynchronous video for a multicultural education course to address the gap between bilingual policy and instructional practice in Indonesian elementary teacher preparation. Methods: A mixed-methods design combined the Four-D development model with a 16-week quasi-experimental pretest–posttest control-group study in which two intact classes totalling 74 pre-service teachers (37 per group) were assigned to conditions without randomization. Data from expert validation questionnaires, a validated cognitive test, structured observations, response questionnaires, and interviews were analysed using ANCOVA, normalized gain, and thematic analysis. Findings: All components of the tools met the expert-validation criterion in the highest (“very valid”) category, with high inter-validator agreement. The experimental group achieved significantly higher covariate-adjusted post-test scores than the control group (adjusted mean difference = 12.14, 95% CI [7.23, 17.04], partial η² = .26), together with a higher class-average normalized gain (g = 0.50 vs. 0.29) and, descriptively, higher mastery attainment (76% vs. 54%). Observed engagement in the experimental group rose across the semester and most students (86.5%) responded positively; lower baseline English proficiency was descriptively associated with non-mastery. Research Implications: The validated tools offer an adaptable template for bilingual teacher education, provided implementation includes diagnostic assessment, differentiated scaffolding for lower-proficiency learners, and reliable technical support. Originality: This study provides rare controlled quasi-experimental evidence from Indonesian teacher education on integrating CLIL, asynchronous video-mediated communication, and multicultural content as one coherent instructional package.